2015
DOI: 10.18632/oncotarget.4697
|View full text |Cite
|
Sign up to set email alerts
|

Twist promotes reprogramming of glucose metabolism in breast cancer cells through PI3K/AKT and p53 signaling pathways

Abstract: Twist, a key regulator of epithelial-mesenchymal transition (EMT), plays an important role in the development of a tumorigenic phenotype. Energy metabolism reprogramming (EMR), a newly discovered hallmark of cancer cells, potentiates cancer cell proliferation, survival, and invasion. Currently little is known about the effects of Twist on tumor EMR. In this study, we found that glucose consumption and lactate production were increased and mitochondrial mass was decreased in Twist-overexpressing MCF10A mammary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 53 publications
6
69
0
Order By: Relevance
“…Hence, Twist is an important stimulating factor in the process of EMT. Some previous studies have shown that the activation of the PI3K/AKT signaling pathway lead to a high level of Twist expression [22,23]. In the present study, we found that Huaier could reverse the EMT in 786-O cells and reduce Twist expression.…”
Section: Discussionsupporting
confidence: 67%
“…Hence, Twist is an important stimulating factor in the process of EMT. Some previous studies have shown that the activation of the PI3K/AKT signaling pathway lead to a high level of Twist expression [22,23]. In the present study, we found that Huaier could reverse the EMT in 786-O cells and reduce Twist expression.…”
Section: Discussionsupporting
confidence: 67%
“…This fact has repeatedly been confirmed in more recent studies [814] indicating that G6PD plays an important role in the metabolism of cancer cells.…”
Section: Supportive Evidencesupporting
confidence: 65%
“…For treatment of Ku60019 (S1570, Selleck Chemicals), an specific oxidized ATM inhibitor, cells were grown to approximately 60% confluence, the culture medium was replaced by fresh medium containing 1 µM, 3µM, 5µM Ku60019 or vehicle for 6 hours. The transfections of the indicated plasmids into cells were performed as described previously [29].…”
Section: Cell Culture Treatments and Transfectionsmentioning
confidence: 99%